ChemInform Abstract: Asymmetric Aldol Reaction of Formaldehyde Catalyzed by Diarylprolinol. Issue 48 (2nd December 2014) - Yasui, Yusuke; Benohoud, Meryem; Sato, Itaru; Hayashi, Yujiro
Abstract A decreasing enantioselectivity is observed with increasing reaction time.